Smart Drugs: from therapy to transhumanism - Ballesteros, Virginia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2018)
Enhancing human cognitive capacities is one of the central axes of transhumanist proposals. In recent decades, halfway between the actual and the possible, another way of approaching human mind enhancement has appeared: smart drugs —also known as cognitive enhancers or nootropics— psychopharmaceuticals that promise an improvement in cognition, memory, intelligence, attention, concentration... These drugs are currently used in the therapeutic field, but many think that the barriers between therapy and human enhancement are fading away. This paper presents three smart drugs —methylphenidate, modafinil and pyracetam— and reflects on the limits between therapy and enhancement, placing special emphasis on the axiological problems entailed.